Development of TRADISKA Smartcard Media Based on Augmented Reality to Improve Social Studies Learning Outcomes of Fourth-Grade Elementary School Students - Diana Shafa Nur Aisyah; Dyan Desi Madyarini (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
Social Studies learning in elementary schools faces challenges because the materials are often abstract, while students are still in the concrete operational stage. This condition causes difficulties in understanding concepts, particularly on traditions and community culture topics, which are further exacerbated by the use of lecture methods and less varied textbooks. This study aimed to develop Smartcard TRADISKA learning media based on Augmented Reality (AR) and to examine its feasibility and effectiveness in improving elementary school students’ Social Studies learning outcomes. The research employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, questionnaires, and learning outcome tests (pretest and posttest), and analyzed using descriptive analysis, N-Gain, and paired sample t-tests. The findings revealed that the AR-based Smartcard TRADISKA media achieved a very high feasibility level, with validation scores of 95% from media experts and 94% from material experts. The media was also proven effective in improving learning outcomes, with an N-Gain score of 70.65% in the large-scale trial, categorized as high. These findings indicate that Augmented Reality-based learning media can improve students’ conceptual understanding of Social Studies more concretely while also enhancing student engagement and learning outcomes in elementary schools.